2014
DOI: 10.4028/www.scientific.net/amr.1051.466
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Forest Fire Hazards Using Data Mining Techniques: Decision Tree and Neural Networks

Abstract: Lebanon is known as a tourist destination for its scenic green mountains but the fires have been threatening this green forestry all over the world. The consequences of forest fires are disastrous on the natural environment and ecological systems, not to mention the population, by worsening poverty and lowering the quality of life. Two data mining techniques are used for the purpose of prediction and decision-making: Decision trees and back propagation forward neural networks. Four meteorological attributes ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The algorithm is based on statistical learning theory and structural risk minimization capable of addressing linear and non-linear multivariate regression problem [187]. SVM separates two opposite analogous hyperplanes and get the best separating distance between two vectors [106,127]. If the space between them is large, then the overall error of the classifier is reduced.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The algorithm is based on statistical learning theory and structural risk minimization capable of addressing linear and non-linear multivariate regression problem [187]. SVM separates two opposite analogous hyperplanes and get the best separating distance between two vectors [106,127]. If the space between them is large, then the overall error of the classifier is reduced.…”
Section: Methodsmentioning
confidence: 99%
“…In some papers, different types of models have been compared in various types of geoscience application. For example SVM and random space in [78,99,103], ANN-fuzzy logic approach [48,61,81,98,104,105]; Decision tree and Neural Networks [77,92,98,105,106] have been applied elsewhere. Reports have shown that some of these approaches out-performed the conventional techniques [49,107,108].…”
Section: Research Backgroundmentioning
confidence: 99%
“…Two strategies of data mining has utilized with the intention of forecast and decision-making, which is Decision trees and back propagation forward neural networks [12]. Temperature, Relative Humidity, Wind Speed and Daily Precipitation are the four meteorological features being utilized.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, scientists worked hardly to predict forest fire in an accurate way by breaking down the non-linear relationship between fire occurrence and surrounding environment. Significant high accuracy performance results were reported using data mining tools such as: neural network [5], [6], fuzzy logic [5], and decision tree techniques [7].…”
Section: Introductionmentioning
confidence: 99%